2005
DOI: 10.1007/s11738-005-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant protoplast technology: Current status

Abstract: 115 9516334; phone +44 115 9513057 Key words: Proto plasts, ge netic ma nip u la tion, nuclear and organelle trans for ma tion, phys i o log i cal in ves ti ga tions, protoplast-to-plant sys tems, so matic hy bridi sa tion ACTA PHYSIOLOGIAE PLANTARUM Vol. 27. No. 1. 2005: 117-129re view liv ing cell con tents into a hypertonic so lu tion. Several years later, what may now be con sid ered as early 'bio tech nol ogy' ex per i ments em a nated from in ves ti ga tions of Kuster (1909) andMichel (1937). These work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 81 publications
2
65
0
Order By: Relevance
“…The calli derived from sLD and liquid culture systems were non-embryogenic, while those derived from aPL culture system showed both embryogenic and non-embryogenic characteristics. The effects of various culture systems on callus formation from protoplasts have also been reported in other plants [7,8,15,24]. In Gentiana kurroo, globular somatic embryos were detected one week after the microcolonies obtained in the thin layer culture and bead culture had been transferred to induction medium, but the cell aggregates obtained in the liquid culture died when transferred to the same medium [15].…”
Section: Plantlet Regenerationmentioning
confidence: 65%
See 1 more Smart Citation
“…The calli derived from sLD and liquid culture systems were non-embryogenic, while those derived from aPL culture system showed both embryogenic and non-embryogenic characteristics. The effects of various culture systems on callus formation from protoplasts have also been reported in other plants [7,8,15,24]. In Gentiana kurroo, globular somatic embryos were detected one week after the microcolonies obtained in the thin layer culture and bead culture had been transferred to induction medium, but the cell aggregates obtained in the liquid culture died when transferred to the same medium [15].…”
Section: Plantlet Regenerationmentioning
confidence: 65%
“…In Ulmus minor, all the proliferating calli derived from the agarose droplet culture acquired the embryogenic characteristics 15 weeks after culture initiation [24]. Previous research suggested that the regeneration potential of the protoplasts in different culture systems might be influenced through stimulating cell wall formation, stabilizing the plasmalemma, supply of nutrients, the dilution of inhibitory substances, etc [7,8]. In this study, the aPL method gave compact colonies with small homogenous cells, which readily turned into embryogenic calli, once transplanted onto subculture medium.…”
Section: Plantlet Regenerationmentioning
confidence: 99%
“…nonionic surfactants or artificial oxygen carriers which enhance physiological status of the cultured cells. Such factors are able to increase plating efficiencies even a fewfold (Davey et al 2005b). In this report we show beneficiary effect of phytosulfokine (PSK) which represents a new class of supplements-the peptide growth factors.…”
Section: Discussionmentioning
confidence: 81%
“…For example, npropyl gallate (nPG) seems to target the first category of phenomena through its antioxidant activity (Saleem and Cutler 1987;Krens et al 1994). In turn, the stimulating effect of nurse cells results from the chemical signals they emit to cultured protoplasts (Hall et al 1993, Davey et al 2005b. It is obvious that phytosulfokine also falls into the second category of factors and once its action was even referred to as chemical nursing (Matsubayashi et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, incubation of protoplasts in liquid medium is the most simple to establish but results in unfavorable cell agglutination (Davey et al 2005a). Therefore, for many species, techniques ensuring physical separation of protoplasts based on their embedding in semi-solid media, with agar being first used as the gelling agent (Nagata and Takebe 1971), have been preferred (Davey et al 2005b).…”
Section: Introductionmentioning
confidence: 99%